Starptautiskās organizācijas un dalībvalstu atbildība par starptautisko tiesību pārkāpumiem - Frīdenbergs-Ansbergs, Kaspars (Latvijas Universitāte, 2007)
Šī diplomdarba mērķis ir analizēt starptautiskās organizācijas un tās dalībvalstu atbildību par starptautisko irganizāciju izdarītajiem pārkāpumiem. Būtiska šī darba daļa ir veltīta starptautiskās organizācijas tiesībsubjektības izvērtēšanai. Tāpat tiek apskatītas galvenās teorijas par starptautisko organizāciju dalībvalsts pārkāpumiem. Autors nonāk pie secinājuma, ka dalībvalstis, neskatoties uz starptautiskās organizācijas tiesībsubjektību, var būt atbildīgas par starptautiskās organizāciajas izdarītajiem pārkāpumiem.

The purpose of the thesis “Responsibility of international organizations and member-states for international erongful acts”is to analyze responsibility of an international organization in connection of the responsibility of the member states of an international organization for international wrongful acts. Main part of this study is dedicated to analyze whether all international organizations have legal personality and whether such legal personality is binding to non-members of the international organization. Moreover several theories on responsibility of member states for act committed by an international organization is being analyzed. The author of this study concludes that members of international organization that has separate legal personality under particular circumstances can be responsible for acts committed by an international organization however examination of factual circumstances of the case should be examined in order to find proper solution for such problem.
Responsibility of international organizations and member-states for international erongful acts
Keywords: Tiesības